2017
DOI: 10.1016/j.freeradbiomed.2017.09.012
|View full text |Cite|
|
Sign up to set email alerts
|

Red/near infrared light stimulates release of an endothelium dependent vasodilator and rescues vascular dysfunction in a diabetes model

Abstract: Peripheral artery disease (PAD) is a morbid condition whereby ischemic peripheral muscle causes pain and tissue breakdown. Interestingly, PAD risk factors, e.g. diabetes mellitus, cause endothelial dysfunction secondary to decreased nitric oxide (NO) levels, which could explain treatment failures. Previously, we demonstrated 670nm light (R/NIR) increased NO from nitrosyl-heme stores, therefore we hypothesized R/NIR can stimulate vasodilation in healthy and diabetic blood vessels. Vasodilation was tested by ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 29 publications
5
49
1
Order By: Relevance
“…We recently established that red light irradiation time-dependently increases dilation of pre-constricted murine facial artery in an NO-dependent, but eNOS-independent manner. Incubation of vessels with the NOS inhibitor L-NAME did not significantly affect vasodilation, however, the NO scavenger cPTIO abolished the effect [22] . These data suggest that red light-stimulated an NO-dependent vasodilation that was largely NOS-independent.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…We recently established that red light irradiation time-dependently increases dilation of pre-constricted murine facial artery in an NO-dependent, but eNOS-independent manner. Incubation of vessels with the NOS inhibitor L-NAME did not significantly affect vasodilation, however, the NO scavenger cPTIO abolished the effect [22] . These data suggest that red light-stimulated an NO-dependent vasodilation that was largely NOS-independent.…”
Section: Resultsmentioning
confidence: 81%
“…In our previous study [22] we showed that irradiation of vessels at 670 nm generates a relatively stable transferable NO-dependent mediator which is released from the endothelium and could dilate a naïve vessel in the dark. We examined if ascorbate pre-treatment would prevent the release of this mediator.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations